A NEW PERSPECTIVE ON AL-JUMLAH ISMIYAH AND FI'LIYAH IN THE CONTEXT OF AL-QAWAID AL-ASASIYAH FI ULUMIL QURAN BY SAYYID MUHAMMAD ALAWY AL-MAKKY - Basid, Abdul (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
This article aims to provide a reinterpretation of the concepts of Al-Jumlah Ismiyah and Fi'liyah in the light of the book "Al-Qawaid Al-Asasiyah Fi Ulumil Quran" by Sayyid Muhammad Alawy Al-Makky. The study explores the significance, methodology, and outcomes of this research. The primary objective of this study is to shed light on the deep insights of Al-Jumlah Ismiyah and Fi'liyah as presented by Sayyid Muhammad Alawy Al-Makky in his seminal work. By examining the core principles and foundations outlined in "Al-Qawaid Al-Asasiyah Fi Ulumil Quran," this research seeks to reevaluate and reinterpret the concepts within a contemporary context. The research methodology employed in this study involves a comprehensive analysis of the book, Al-Qawaid Al-Asasiyah Fi Ulumil Quran, by Sayyid Muhammad Alawy Al-Makky. The text is examined to identify the key principles and explanations provided regarding Al-Jumlah Ismiyah and Fi'liyah. The findings are then critically analyzed, taking into consideration relevant sources and scholarly discussions to offer a fresh perspective on these concepts. The benefits of this research lie in its potential to enhance our understanding of Al-Jumlah Ismiyah and Fi'liyah and their applications within the realm of Quranic studies. By reinterpreting these concepts, scholars and researchers can gain new insights into Arabic grammar, syntax, and Quranic exegesis. The findings of this study may contribute to the development of more comprehensive methodologies for understanding the linguistic and grammatical aspects of the Quran. The results of this research reveal a nuanced understanding of Al-Jumlah Ismiyah and Fi'liyah. Through the reinterpretation of Sayyid Muhammad Alawy Al-Makky's insights, it becomes evident that these concepts possess broader implications for understanding the structure and coherence of the Quranic text. The findings encourage further exploration and investigation, inviting scholars to delve deeper into the intricacies of Quranic language and its implications for Quranic interpretation. In conclusion, this article presents a reinterpretation of Al-Jumlah Ismiyah and Fi'liyah based on the perspectives provided in the book "Al-Qawaid Al-Asasiyah Fi Ulumil Quran" by Sayyid Muhammad Alawy Al-Makky. By examining the goals, benefits, methodology, and outcomes of this research, it contributes to a broader understanding of these concepts and their significance within the field of Quranic studies.